Examining social accountability tools in the water sector: a case study from Nepal - Dhungana, H.; Clement, Floriane; Otto, B.; Das, B. (International Water Management Institute, 2021)
Enhancing accountability has become an important objective of the governance reforms over the past two decades. Yet, only a few studies have explored the use of social accountability tools in the water sector in particular. This report aims to fill this gap, based on a case study of a donor-funded water, sanitation and hygiene (WASH) program in Nepal. We document and analyze the effects of two types of social accountability tools implemented by the program: public hearings and social audits. We examined how these tools have contributed to increased transparency, participation, voice and accountability, and in turn discuss their potential to reduce corruption. We relied on qualitative methods to collect data in two case study water supply schemes in two districts of Nepal. The study found that the social accountability tools provided a platform for water users to participate and deliberate on issues related to the execution of WASH schemes. However, the scope of accountability narrowly focused on the integrity of the water user committees but did not provide the political resources and means for communities to hold funding and implementing agencies accountable. Furthermore, attention to budget management has not provided space to address environmental and social justice issues related to payment of wages, access to water and decision-making processes in the design of the water scheme and water allocation. Findings from the study also indicate that the concept of deliberation and downward accountability, as envisioned in international development discourses, does not necessarily match with local power relationships and local cultural norms.